Biodegradação de tocos de Eucalyptus sp. pela ação de cupins xilófagos - Chagas, Thiago Xavier (2016)
Eucalyptus plantations can be managed under the cutting regime and retirement or coppice. After harvest there is the remnants’ accumulation of hard degradation culture, including the stump. This forest residue can be a micro-habitat and abundant food source for termites. The identification of termites’ species that occur at stumps can be a viable alternative to accelerate the process of degradation, assisting in partial or total removal. The aim of the study was to identify species of termites in stumps of Eucalyptus urograndis and evaluate its biodegradation in areas with two and four years old after cutting. The study was conducted in two areas, with aftercut ages of two and four years, located in the city of Entre Rios, Bahia, Brazil. The stumps were fragmented, with the aid of a cutter, and termites collected and deposited in 15 ml Falcon tubes, containing 80% alcohol. The termites were identified by key taxonomic aid and comparisons among copies from the base collection of Forest Entomology Laboratory of the Federal University of Sergipe, and the Zoology Museum of the University of Sao Paulo. The measurement of the diameter and height of the stumps were performed before and after fragmentation. After this measurement, the initial volume and the final volume of the stumps were calculated, to determine their biodegradation. To evaluate stumps’ biodegradation in the aftercut ages, data were analyzed by SAS 9.0 software, using the ANOVA for comparison. Seven species of termites, which belongs to four genera in the Termitidae family, were collected. Nasutitermes corniger, N. kemneri and Amitermes amifer were dominants. In the stumps biodegradation analysis was verified a significant difference between the afetrcut ages of two and four years. It is possible to find termites in stumps of Eucalyptus urograndis foraging alone or associated with other species. They are able to biodegrade stumps of Eucalyptus urograndis areas aged two and four years after cutting. There is an increasing trend in biodegradation of the stumps in area with higher post-crop age, as observed in the area with four years of age.